Polygene inheritance of latex yield in Hevea brasiliensis Muell. Arg. - Omokhafe Kenneth Ohi; Nasiru Ibrahim (Plant Genetic Resources News Letter, 2004)
One-hundred-and-thirty hybrids of Hevea brasiliensis were evaluated for polygene inheritance of latex yield. The hybrids were cloned by budding and evaluated in field trials. Clonal latex yield in grams per tree per tapping (g t-1 t-1) was evaluated in four years. Log10 transformation of clonal g t-1 t-1 was performed. The transformed clonal g t-1 t-1 in each year and cumulative mean were tested for conformity with phenotypic distribution of 5, 7, 9 and 11 classes corresponding to 2, 3, 4 and 5 segregating polygenes, respectively. There was consistent agreement between observed and expected phenotypic distributions for nine phenotypic classes. This means that four polygenes control the inheritance of latex yield in H. brasiliensis. Selection of hybrids of H. brasiliensis for all the dominant genes responsible for high latex yield will therefore require a proportion of one out of 256 in a pool of hybrids. This will ensure that all the selected hybrids are free of any recessive alleles for latex yield.
Keywords: Hevea brasiliensis; Latex; Rubber; Yield polygene inheritance